A Comparison of Energy Expenditure and Heart Rate Response Between a Dance-Based Group Fitness Class and a Dance-Based Video Game on the Xbox Kinect. Issue 2 (April 2016) - Eason, Jane M.; York, Ashlee; LeJeune, Casey; Norris, Stefan
Abstract : Purpose: To compare the energy expenditure between a dance-based group fitness class and a dance-based video game on the Xbox Kinect. Methods: This was a crossover design in which thirty healthy female subjects participated in an hour long group dance class and an hour long playing session of Just Dance 3 and Just Dance 4 for the Xbox Kinect gaming system. Heart rate and caloric expenditure were recorded through a heart rate monitor and a triaxial accelerometer, respectively, throughout the sessions. Rating of perceived exertion scores were collected at the end of each session. Results: There was no difference in resting heart rate between both modes of exercise ( P = .171). Average heart rate and calories expended were both significantly greater ( P = .006 and P = .0001, respectively) in the dance class as compared with the Xbox Kinect. Rating of perceived exertion was significantly greater ( P = .0001) in the dance class as compared with the Xbox Kinect. Conclusions: The results indicate that the dance-based group fitness class elicits a significantly greater intensity across several key measures as compared with the dance-based video game. Although the dance-based fitness class was superior to the Kinect sessions in terms of increasing heart rate and energy expenditure, 96.67% of subjects still demonstrated an increase in peak heart rate to over 50% of age-predicted heart rate maximum while playing the Xbox Kinect.